Innovative strategy development for supporting sustainable tourism in Latvia - Dehtjare, J.; Mironova, J.; Balode, I. (НТУ ДП, 2022)
The Covid-19 pandemic has negatively impacted the many different sectors of tourism, ultimately causing the world industry to shut down for almost two years. Though various efforts have been made since June 2020 to reopen the industry, most sectors continue to struggle and the UNWTO has acknowledged tourism as one of the hardest hit industries (Collins-Kreiner & Ram, 2021). Crises are regular occurrences in tourism (Dolnicar & Zare, 2020). Many destinations are affected by natural and human-made crises and, over the years, have developed tactics and strategies of resilience and mitigation (Ritchie & Yaing, 2019).
Keywords: innovative strategy